Piloting a Faculty Development Program in a Rural Haitian Teaching Hospital. Issue 1 (9th March 2022) - Hudspeth, James C.; Gangasani, Nikitha; Julmisse, Marc; Israel, Kerling; Marcelin, Naomie; Raymond, Nadia; Robert, Merly; Sacks, Zadok; Curry, Christine L.; Morse, Michelle
Background: Faculty development for nurse and physician educators has a limited evidence base in high income countries, and very little research from low- and middle-income countries. Health professions educators in many global settings do not receive training on how to educate effectively. Objective: To pilot and assess a faculty development program aimed at nurse and physician educators at a teaching hospital in rural Haiti. Methods: We developed a program covering a total of 22 topics in health professions education, including applied learning theory as well as nurse and physician targeted topics. We assessed impact through participant assessment of personal growth, participant evaluation of the program, knowledge testing pre and post program, and structured observations of program participants providing teaching during the program. Findings: Nineteen out of 37 participants completed the program. While participant reviews were uniformly positive, a pre- and post-test on general educational topics showed no significant change, and the effort to institute observation and feedback of teaching did not succeed. Conclusions: Our project showcases some benefits of faculty development, while also demonstrating the challenges of instituting faculty development in situations where participants have limited time and resources. We suspect more benefits may emerge as the program evolves to fit the learners and setting.